2022
DOI: 10.7150/jca.61961
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA PCAT19 induced by SP1 and acted as oncogene in gastric cancer competitively binding to miR429 and upregulating DHX9

Abstract: Increasing evidence suggests that long non-coding RNAs (lncRNAs) are crucial in cancer biological processes. To investigate if lncRNA contributes to gastric cancer (GC), we conducted a bioinformatics analysis in human microarray datasets, and the results showed that lncRNA prostate cancer-associated transcript 19 (PCAT19) was upregulated in GC. Quantitative reverse-transcriptase PCR and in situ hybridization assays also revealed that PCAT19 was upregulated in GC tissues. The PCAT19 expression in GC was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…[25] Moreover, some studies showed that PCAT19 is implicated in PCa cell growth and tumor progression. [26][27][28] The nature of TME in the evolution of cancer has changed our understanding of cancer development. [29,30] A wide variety of immune and non-immune cells within the TME infrastructure, together with the factors that they secrete, cooperate to create a chronic inflammatory, immunosuppressive, and protumoral environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Moreover, some studies showed that PCAT19 is implicated in PCa cell growth and tumor progression. [26][27][28] The nature of TME in the evolution of cancer has changed our understanding of cancer development. [29,30] A wide variety of immune and non-immune cells within the TME infrastructure, together with the factors that they secrete, cooperate to create a chronic inflammatory, immunosuppressive, and protumoral environment.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Moreover, some studies showed that PCAT19 is implicated in PCa cell growth and tumor progression. [26–28]…”
Section: Discussionmentioning
confidence: 99%
“…We also performed lncRNA microarray analysis in 5 paired gastric cancer tissues of our institution to detect the lncRNA expression profile. We have already described the processing and analysis of data in the previous study [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…LncRNAs have been found to be involved in a variety of biological processes, can act as oncogenes or tumor suppressors, and are associated with various aspects of cancer, including tumorigenesis, metastasis, and treatment resistance [15][16][17][18][19]. The aberrant expression patterns of lncRNAs in GI cancers have been linked to clinical outcomes, making them promising tumor markers and potential therapeutic targets [11,[20][21][22][23][24][25][26].…”
Section: Ivyspringmentioning
confidence: 99%